Breastfeeding and Human Lactation - Perrella, Sharon (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
Human lactation has evolved to produce a milk composition that is uniquely-designed for the human infant. Not only does human milk optimize infant growth and development, it also provides protection from infection and disease. More recently, the importance of human milk and breastfeeding in the programming of infant health has risen to the fore. Anchoring of infant feeding in the developmental origins of health and disease has led to a resurgence of research focused in this area. Milk composition is highly variable both between and within mothers. Indeed the distinct maternal human milk signature, including its own microbiome, is influenced by environmental factors, such as diet, health, body composition and geographic residence. An understanding of these changes will lead to unravelling the adaptation of milk to the environment and its impact on the infant. In terms of the promotion of breastfeeding, health economics and epidemiology is instrumental in shaping public health policy and identifying barriers to breastfeeding. Further, basic research is imperative in order to design evidence-based interventions to improve both breastfeeding duration and women's breastfeeding experience.